Evaluasi Penanganan Nyeri Haid (Dysmenorrhea) Dengan Protection Motivation Theory - Tasya Haditya; Mardlatillah Mardlatillah; Farah Nur Ain; Nur Syifa; Muhammad Akhzani Fadhli (Jurnal Pelayanan Kefarmasian dan Sains, 2022)
Background: Menstruation, known as menstruation or menstruation, is a physiological change in women that occurs periodically and is influenced by reproductive hormones, starting from menarche to menopause (Syafrudin, 2011). Abnormalities or disorders related to menstruation include premenstrual tension (tension before menstruation), mastodynia (pain in the breasts), mittelschmerz (pain during ovulation), and dysmenorrhea (pain during menstruation). Menstrual pain (dysmenorrhea) is one of the disorders that causes young women to go to the doctor for consultation and treatment. Menstrual pain or called Dysmenorrhea is pain that usually arises in adolescence, which is about 2 to 3 years after the first menstruation. Menstrual pain is a complaint that is often experienced by adolescents in the lower abdomen (Kusmiran, 2013). Menstrual pain makes women unable to carry out their normal activities and requires prescription drugs. This situation causes a decrease in the quality of life of women, for example female students who experience primary menstrual pain cannot concentrate on learning and learning motivation decreases because of the pain they feel. Objective: To see and evaluate the behavior of sufferers of menstrual pain (dysmenorrhea) in carrying out protective behavior (protection motivation theory) Methods: An evaluative study that aims to see the rationale for handling menstrual pain (dysmenorrhea) in students of the Faculty of Health, Sari Mulia University, Banjarmasin. The approach used in this research design is a cross sectional study where data is collected at a certain time. Data collection was carried out at the Faculty of Health, Sari Mulia University, Banjarmasin in April-May 2021. Results: In this project, research has been carried out on the Evaluation of Menstrual Pain Management (Dysmenorrhea) with the Protection Motivation Theory. We distributed 21 questions and got 80 respondents from various departments and semesters in the health faculty, namely 51.2% pharmacy students, 28.7% nursing students, 13.7% midwifery students and 6.3% health promotion students. The 80 respondents also consisted of 52.5% 4th semester students, 31.3% 2nd semester students, 12.5% 6th semester students and 3.7% 8th semester students. The age range of the respondents was 18-22 years old. Conclusion: Respondents make efforts to protect themselves from menstrual pain (dysmenorrhea) that is felt by doing therapy, both pharmacologically and non-pharmacologically. Respondents try to do rational treatment such as using the right dose, frequency, and proper use.